Ray Tracing Gems II Next Generation Real-Time Rendering with DXR, Vulkan, and OptiX - Marrs, Adam; Shirley, Peter; Wald, Ingo (Apress : Imprint: Apress, 2021)
This Open Access book is a must-have for anyone interested in real-time rendering. Ray tracing is the holy grail of gaming graphics, simulating the physical behavior of light to bring real-time, cinematic-quality rendering to even the most visually intense games. Ray tracing is also a fundamental algorithm used for architecture applications, visualization, sound simulation, deep learning, and more. Ray Tracing Gems II is written by industry experts with a particular focus on ray tracing, and it offers a practical means to master the new capabilities of current and future GPUs with the latest graphics APIs. What You'll Learn: The latest ray tracing techniques for developing real-time applications in multiple domains Case studies from developers and studios who have shipped products that use real-time ray tracing. Guidance, advice and best practices for rendering applications with various GPU-based ray tracing APIs (DirectX Raytracing, Vulkan Ray Tracing) High performance graphics for 3D graphics, virtual reality, animation, and more.